"LIQUENS EM CAPÕES DO PANTANAL SUL-MATO-GROSSENSE E SUA RELAÇÃO COM O FOGO" - MATHEUS MAGALHÃES HENRIQUES DO AIDO (2023)
A study of the lichen communities at Pantanal known as "capões" was performed. Two new lichen species are described as new from the Pantanal biome in Brazil, viz. Crypthonia quinqueseptata and Lithothelium aggregatum.